PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT MAXPLUS INDONESIA ANUGERAH JAKARTA - Nuraida, Asyka; Andriani, Jeni (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of work stress on employee performance, to determine the effect of work motivation on employee performance, to determine the effect of work stress and work motivation simultaneously on employee performance at PT Maxplus Indonesia Anugerah. The method used is associative quantitative. The sampling technique used was saturated with a sample of 53 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, correlation analysis, multiple linear regression analysis. The results of this research are that work stress has a sig of 0.000 <0.05, so Ho is rejected and Ha is accepted, which means that work stress has a significant and significant effect on employee performance. Work motivation has a sig of 0.000 > 0.05, so Ho is accepted and Ha is rejected, which means work motivation has no effect and is not significant on employee performance. F count 45,206>3.18 and sig 0.000 <0.05, then Ho is rejected and Ha is accepted, then Ho is rejected, Ha is accepted, which means that work stress and work motivation have a simultaneous and significant effect on employee performance. Effective work stress and good work motivation will be able to improve employee performance.